al-Taʿlīm wa-al-Thaqāfah Wasīlatān li-al-Daʿwah al-Islāmiyyah: Musāhamāt Anregurutta Ambo Dalle al-Ḥaḍāriyyah - Hilmi Muhammadiyah; Zainal Abidin Husain (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study examines the transformative agency of Anregurutta Ambo Dalle (c. 1896–1996) in constructing a resilient architecture of moderate Islamic education in Eastern Indonesia. Moving beyond conventional biographical accounts, it analyzes his leadership strategies through a multidisciplinary framework integrating diffusion of innovations theory, communication accommodation theory, and cultural hegemony. Employing a qualitative historical case study based on primary and secondary sources, the study identifies three interdependent strategies. First, Ambo Dalle enabled institutional diffusion through the hybridization of traditional and modern pedagogies within the Darud Da’wah wal Irsyad (DDI) network. Second, he pursued deliberate cultural accommodation by employing Bugis linguistic codes and the local authoritative title anregurutta, fostering voluntary value internalization while reducing social resistance. Third, the study highlights his pragmatic yet controversial political alignment with Golongan Karya (Golkar) in 1977. Rather than political opportunism, this affiliation is interpreted as a survival strategy that safeguarded DDI’s institutional continuity under the New Order regime and helped normalize Islamic moderation (wasathiyah) as cultural common sense. Overall, the findings demonstrate that intellectual actors can sustainably institutionalize religious moderation through context-sensitive strategies combining educational reform, cultural translation, and tactical political engagement, as evidenced by the enduring DDI network in pluralistic postcolonial contexts of the Global South.